An evaluation of the Philippine Normal College Bachelor of Science on Elementary Education degree preparation of public elementary school teachers of the Division of Rizal - Vicencio, Evelina Maclang (1965)
This study is an opinion survey of 128 public elementary school teachers employed in the Division of Rizal who graduated from the Philippine Normal University in 1960, 1961, and 1962 toward their experiences as provided for in the Bachelor of Science in Elementary Education curriculum. It covers 4 phases of the teacher education program: general education, professional education, professional laboratory experiences, and co-curricular activities. On the basis of the findings of the study, the general education program courses may be broadened to include Public Speaking, more intensive English, General Psychology, and more science courses.